2021
DOI: 10.7570/jomes21056
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Fact Sheet in Korea, 2020: Prevalence of Obesity by Obesity Class from 2009 to 2018

Abstract: Lee 4,* , on behalf of the Taskforce Team of the Obesity Fact Sheet of the Korean Society for the Study of Obesity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 23 publications
2
50
0
1
Order By: Relevance
“…In several developed countries, the prevalence of morbid obesity has been reported to quadruple as the obesity prevalence doubled. 9 This trend has also been reported in South Korea; an article by Nam et al 2 in this issue reported that the overall prevalence of obesity has increased during recent years and, moreover, the prevalence of class II and III obesity has also significantly increased in the population as a whole as well as nearly all age and sex groups based on the 2020 Obesity Fact Sheet by KSSO. 2 …”
supporting
confidence: 58%
See 2 more Smart Citations
“…In several developed countries, the prevalence of morbid obesity has been reported to quadruple as the obesity prevalence doubled. 9 This trend has also been reported in South Korea; an article by Nam et al 2 in this issue reported that the overall prevalence of obesity has increased during recent years and, moreover, the prevalence of class II and III obesity has also significantly increased in the population as a whole as well as nearly all age and sex groups based on the 2020 Obesity Fact Sheet by KSSO. 2 …”
supporting
confidence: 58%
“… 1 The BMI cutoff for obesity in Asians is ≥25 kg/m 2 and the Korean Society for the Study of Obesity (KSSO) categorizes a BMI of 25.0–29.9 kg/m 2 , 30.0–34.9 kg/m 2 , ≥35.0 kg/m 2 as class I, II, and III obesity, respectively. 2 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, the prevalence of risk factors for CVD, such as diabetes, hypertension, obesity, and dyslipidemia, has been steadily increasing in Koreans. According to the Obesity Fact Sheet released by Korean Society for the Study of Obesity in 2020, based on NHIS data in 2018, the prevalence of obesity in Korea was 32.5% [ 4 ]. According to the Diabetes Fact Sheet released by the Korean Diabetes Association (KDA) in 2020, the prevalence of diabetes was 13.8% in Koreans older than 30 years, based on 2018 data from the Korean National Health and Nutrition Examination Survey [ 9 ].…”
Section: Trends In the Prevalence Of Obesity And Diabetes In Korea An...mentioning
confidence: 99%
“…Obesity is renowned for its tendency to be accompanied by comorbid diseases, such as diabetes, atherosclerosis, metabolic syndrome (MS), and sleep apnea [ 1 – 3 ]. The prevalence of obesity in adults older than 30 has reached 30% worldwide, and this high rate of obesity is particularly pronounced in Asians, due to rapid changes in dietary patterns and a sedentary lifestyle [ 4 ].…”
Section: Introductionmentioning
confidence: 99%